The Vital Link Between Chronic Disease and Depressive Disorders - Daniel P. Chapman, PhD; Geraldine S. Perry, DrPH; Tara W. Strine, MPH (Centers for Disease Control and Prevention, 2005)
Introduction Chronic diseases have assumed an increasingly important role in public health research and intervention. Without treatment, depressive disorders characteristically assume a chronic course and are expected, by 2020, to be second only to heart disease in the global burden of disease. Thus, understanding the relationship between depressive disorders and chronic disease appears vital to public health assessment and health care delivery. Methods Articles for review were primarily identified by a Medline search emphasizing the subject headings mental disorders or depression crossed with selected chronic diseases and conditions including asthma, arthritis, cardiovascular disease, cancer, diabetes, and obesity. Results Mental illnesses most specifically, depressive disorders were associated with increased prevalence of chronic diseases. This association between depression and chronic disease appears attributable to depressive disorders precipitating chronic disease and to chronic disease exacerbating symptoms of depression. The complex interrelationship between depressive disorders and chronic disease has important implications for both chronic disease management and the treatment of depression. Conclusion Depressive disorders assume an important role in the etiology, course, and outcomes associated with chronic disease. Multivariate community-based research and intervention fostering the detection and treatment of depressive disorders is needed, as is further examination of the role exerted by mental illnesses other than depression in the pathogenesis of chronic disease.